2016
DOI: 10.1002/bit.25914
|View full text |Cite
|
Sign up to set email alerts
|

Itaconic acid production from glycerol using Escherichia coli harboring a random synonymous codon‐substituted 5′‐coding region variant of the cadA gene

Abstract: Aspergillus terreus cadA, encoding cis-aconitate decarboxylase, is an essential gene for itaconic acid (IA) biosynthesis, but it is primarily expressed as insoluble aggregates in most industrial hosts. This has been a hurdle for the development of recombinant strategies for IA production. Here, we created a library of synonymous codon variants (scv) of the cadA gene containing synonymous codons in the first 10 codons (except ATG) and screened it in Escherichia coli. Among positive clones, E. coli scvCadA_No8 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 22 publications
(24 reference statements)
0
31
1
Order By: Relevance
“…1). Other studies have indicated the importance of cadA expression for itaconate production1920. E. coli BL21(DE3) containing acn and three cadA genes yielded a much higher conversion (64.0%).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…1). Other studies have indicated the importance of cadA expression for itaconate production1920. E. coli BL21(DE3) containing acn and three cadA genes yielded a much higher conversion (64.0%).…”
Section: Discussionmentioning
confidence: 95%
“…produced itaconate using an E. coli strain expressing heterologous cadA , achieving a titer of 690 mg/L18. Another E. coli strain with random synonymous codon substitutions produced 7.23 g/L of itaconate19. Model-based metabolic engineering of E. coli increased itaconate production to 32 g/L20.…”
mentioning
confidence: 99%
“…Recently, Yang et al [102] reported that co-expression of aconitase (ACO) and CAD in E. coli (uCA) resulted in the production of 117.2 mg IA L −1 after 48 h fermentation while the IA titer was significantly improved to 222.1 mg L −1 by self-assembly of ACO-PDZ (APd) and CAD-PDZlig (CPI) in E. coli (sPP) under the same conditions. Jeon et al [35] reported IA production from glycerol using E. coli harboring a random synonymous codon-substituted 5ʹ-coding region variants of the cadA gene. They showed that functional expression of the cadA gene was improved through synonymous codon substitution at the first ten codons (excluding ATG).…”
Section: Recombinant Microorganisms For Production Of Itaconic Acidmentioning
confidence: 99%
“…It may be due to the high shear rate generated by mechanical agitation in the STR that may damage fungal cells. Optimum balance between aeration rate and agitation speed needs to be maintained to avoid mechanical stress on the mycelia caused by excessive impeller speed, or conversely poor oxygen transfer rate at lower speed. Hence, agitation and aeration rates were simultaneously varied in the current investigation to find the optimum balance.…”
Section: Discussionmentioning
confidence: 99%